Allelopathic potential of tropical plants—a review - Motmainna, Mst.; Juraimi, Abdul Shukor; Ahmad-Hamdani, Muhammad Saiful; Hasan, Mahmudul; Yeasmin, Sabina; Anwar, Md. Parvez; Islam, A. K. M. Mominul (Multidisciplinary Digital Publishing Institute, 2023)
The need to meet food demand becomes more urgent as it is forecasted to increase by 50 over the next century. Thus, agronomists promote sensible tools and approaches to eradicate factors that hamper crop production, mainly weeds. The constant use of chemical herbicides to control weeds leads to an increased risk of herbicide-resistant weed populations, environmental pollution, unsafe agricultural products, and negative effects on human health. These problems have caused an interest among researchers to replace synthetic herbicides with alternatives. The purpose of this review was to present the current knowledge base on allelopathic tropical plants and their potential for use in the development of natural product-based, environmentally friendly herbicides for sustainable agriculture, and to stimulate future discussion on this topic. The defence mechanisms of tropical plants have received particular attention because of their potential weed control ability as a natural pesticide that can prevent the overuse of synthetic pesticides. The ancient knowledge of the toxic properties of various tropical plants gives us a basis for creating a novel pest control approach. The synthesis of biopesticides based on allelochemicals opens up the possibility of utilizing natural compounds in crop protection and demonstrates the ability to deal with evolved pesticide resistance.